THE SOUL (AL-NAFS) IN THE PERSPECTIVE OF ISLAMIC THOUGHT - Rosalina, Tita (Archipelago Journal of Southeast Asia Islamic Studies, 2023)
This research discusses nasf or lust is often interpreted as something that always invites ugliness, toxicity and tyranny. Nafs are also always used as scapegoats in every oversight committed by mankind, even lust is also considered a friend of the sheikh. The quality of lust can go down and can go up depending on the behavior of the owner of the lust itself. If the nafs are often sanctified with mujahadah and riyadlah, then the nafs will invite to good, but if the nafs are never sanctified, then the nafs will decrease in quality and tend to invite to ugliness. The focus in this study is how is the essence of nafs (soul)? What is the concept of nafs according to the Qur'an?. The method used in this research is a type of literature research with a historical approach. The result of this study is that Nafs in the context of the Quranic talk about man points to the inner side of man who has good and bad potential, and can encourage him to be able to do good and bad. It must be remembered, however, that the Qur'an in talking about the inner side of man also uses other terms, such as al-aql, al-qalb, al-ruh, and al-fitrah